North Korean policy of B. Obama administration: failures and achievements - Погорєлова І. (Видавничо-поліграфічний центр "Київський університет", 2016)
On the basis of the official American sources analyses, the views of the leading US researchers the policy of Barack Obama democratic administration regarding North Korean nuclear issue is examined. The evolution of American foreign policy towards the states of Korean peninsula during two terms of Obama administration with distinguishing achievements and failures of the democratic team in the noted sphere is observed.

На основі аналізу офіційних американських джерел, поглядів провідних американських дослідників розглянуто ставлення демократичної адміністрації Б. Обами стосовно північнокорейської ядерної проблеми. Простежено еволюцію зовнішньої політики США щодо держав Корейського півострова впродовж двох каденцій адміністрації Б. Обами, із виокремленням здобутків і прорахунків демократичної команди.
Північнокорейська політика адміністрації Б. Обами: прорахунки та здобутки
Keywords: USA; DPRK; nuclear weapons; American-South Korean alliance; США; КНДР; ядерна зброя; американсько-північнокорейський альянс